Ectopic thyroid mass in mediastinum with normal thyroid function and location - Madavi, Adesh; Thakur, Lokendra Singh; Kor, Akshay; Tayade, Kamlesh (Indian Journal of Case Reports, 2024)
There are very few cases of mediastinal ectopic thyroid reported in the literature. An asymptomatic 49-year-old woman with a mediastinal mass is the subject of this report. Mediastinal ectopic thyroids’ epidemiology, clinical manifestations, diagnosis, and treatment were also discussed. A mediastinal ectopic thyroid ought to be viewed as a differential finding among all mediastinal masses. Careful extraction is suggested for both the analysis and treatment of this condition in light of its true capacity for harm and pressure on mediastinal structures. The clinical significance of mediastinal ectopic thyroid is demonstrated in this case.